Against underdog metaphysics : Alvin Gouldner and the Marxist critique of post-theory - Wilén, Carl ; 0000-0002-1408-2866; Söderberg, Johan (Acta Sociologica (United Kingdom), 2025)
A major target of the Marxist critique of “post-theory”—a broad term encompassing post-structuralism, post-Marxism, and postcolonial theory—has been its notorious deconstruction of the subject. The affirmation of marginal, excluded, and deviant subject positions within the same corpus has been noted less frequently. To recalibrate the Marxist critique of post-theory to also encompass its affirmative moment, we consult Alvin Gouldner and his overlooked concept of “underdog metaphysics.” Far from representing a mere mistake or theoretical incoherence, we maintain that the endorsement of the underdog position adds critical, political, and ethical relevance to post-theory, which would be absent from a purely deconstructivist stance. We use Gouldner to connect the reservations that Marxists have long expressed about the revolutionary potential of the lumpenproletariat with the Marxist critique of post-theory. We argue that underdog metaphysics is just as incompatible with a Marxist program of class-based collective action and mobilization of a mass movement as a full deconstruction of the subject. Ultimately, we claim that post-theory combines deconstruction (of the subject) with affirmation (of the underdog) in a two-pronged assault on the Marxist assertion that the emancipation of the working class must be the act of the working class itself. It is therefore unfortunate that most Marxist critics of post-theory have focused on attacking the notion of a decentered subject while overlooking the affirmation of the underdog position.
Keywords: deconstruction; left realist criminology; lumpenproletariat; Marxism; post-theory; standpoint theory; Underdog metaphysics